How Does the Distance Tandem Help the Learning Motivation? - Ainur Rosyidah; Primardiana Hermilia Wijayati (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2019)
This research aims to describe the students’ learning motivation and the effect of a tandem on distance on their writing skill. This research applied the descriptive quantitative method with two instruments. To gather the data, the researcher used questionnaires about learning motivation, tandem, and writing skill and documentation. The sample of this research are the 62 students who took the course German at B2 Level. Based on the result it can be concluded, that the learning motivation of the students is relatively good. However, there are some learning motivation’s aspects, which were not fulfilled. Those are the lack of positive mindset about the language, confidence, feedbacks from the lecturers, and the application of the target language. It was found, that tandem can be a solution to those mentioned problems and increase the learning motivation. The students also learn the German’s culture and get used to communicate with native speakers.